2023
DOI: 10.1002/ejic.202300038
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Fe(III) and Ga(III) Derived from the Cyclic 6‐ and 7‐Membered Hydroxamic Acids Found in Mixed Siderophores

Abstract: Six‐ and seven‐membered cyclic hydroxamic acids are found as terminal binding units in different families of siderophores, including exochelins and mycobactins. The simplest models of these preorganized chelating ligands were known, but their coordination chemistry with Fe3+, the target metal ion of siderophores, had never been reported. Four complexes were synthesized and studied: two Fe3+ complexes, one with the six‐membered ring hydroxamate PIPO− and one with the seven‐membered ring hydroxamate AZEPO−, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
2
0
0
Order By: Relevance
“…They are all constructed from the same basic node of In 3+ chelated by three hydroxamate groups from three TDHA ligands, but variations in coordination modes and (θ) angles led to very different outcomes. The robust formation of identical Ga/In­(hydroxamate) 3 nodes in these MOMs suggested that these moieties were stable and favored, concurring with previously reported hydroxamate-chelated Group 13 metal complexes. , Moreover, similar phenomena were recorded in the MOF literature where identical PBUs/SBUs could be interconnected by ligands of the same basic geometry to form diverse topologies. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…They are all constructed from the same basic node of In 3+ chelated by three hydroxamate groups from three TDHA ligands, but variations in coordination modes and (θ) angles led to very different outcomes. The robust formation of identical Ga/In­(hydroxamate) 3 nodes in these MOMs suggested that these moieties were stable and favored, concurring with previously reported hydroxamate-chelated Group 13 metal complexes. , Moreover, similar phenomena were recorded in the MOF literature where identical PBUs/SBUs could be interconnected by ligands of the same basic geometry to form diverse topologies. …”
Section: Resultssupporting
confidence: 88%
“…The robust formation of identical Ga/In-(hydroxamate) 3 nodes in these MOMs suggested that these moieties were stable and favored, concurring with previously reported hydroxamate-chelated Group 13 metal complexes. 37,38 Moreover, similar phenomena were recorded in the MOF literature where identical PBUs/SBUs could be interconnected by ligands of the same basic geometry to form diverse topologies. 39−42 For SUM-82, NH 3 •H 2 O was a key factor in the reaction between In(NO 3 ) 3 •4.5H 2 O and H 2 -TDHA when used as a modulator (Figure 3a).…”
Section: ■ Results and Discussionsupporting
confidence: 67%